Synthesis of aromatic monopyrrolo-tetrathiafulvalene derivatives with variable degree of π‐conjugation - Mncwangi, Sibusiso Nicko (University of the Free State, 2021)
Tetrathiafulvalene (TTF, 1) and its derivatives have attracted much interest and found widespread applications in molecular, supramolecular and materials chemistry.⁽¹⁾ Monopyrrolo‐tetrathiafulvalenes (MPTTF, 59) possess more extended π–system in comparison to the parent TTF 1, better π–stacking capability and, therefore, they are capable of forming stronger charge‐transfer complexes with molecular acceptors.⁽²⁾
Dissertation (M.Sc.(Chemistry))--University of the Free State, 2021